Holocene sedimentary environments in Smeerenburgfjorden, Spitsbergen - Velle, Julie Heggdal (Universitetet i Tromsø, 2012)
Multi-proxy analyses of six sediment cores (including lithostratigraphy, physical properties, granulometric analyses, and XRF scanning), and analyses of swath bathymetry and chirp data were integrated to elucidate the Holocene sedimentary processes and palaeoenvironments in Smeerenburgfjorden, northwest Spitsbergen. Three basins separated by two sills define the present-day large-scale bathymetry. A transverse ridge in the innermost part of the fjord represents the Little Ice Age (LIA) maximum position of Smeerenburgbreen. Slide scars along the fjord sides and mass transport deposits in the basins indicate repeated mass wasting. Recessional moraines deposited during the last deglaciation suggest a mean annual retreat rate of 140 m/year. Another set of recessional moraines deposited between the maximum LIA position of Smeerenburgbreen and its present day terminus indicate a mean retreat rate of the ice front of ~87 m/year. Although only some of the recessional moraines deposited during the last deglaciation are expressed on the modern seafloor, chirp data reveal that they occur throughout the entire fjord. Suspension settling, ice rafting and mass wasting are the main sedimentary processes acting in Smeerenburgfjorden. Suspension settling is most important in the inner parts of the fjord, resulting in high sedimentation rates that rapidly decrease with increasing distance from the main sediment sources. Strong out-fjord decreasing trends in magnetic susceptibility and Fe-content indicate that these properties are related to material originating from the Hornemantoppen granite in the catchment of Smeerenburgbreen and are, thus, useful proxies for the reconstruction of the activity of the glacier. Relatively little ice rafting, most likely related to warmer surface water conditions, occurred between 8650 and 7350 cal. years BP. Ice rafting from both sea-ice and icebergs increased around 6200 cal. years BP and peaked at ~5200 cal. years BP, associated with a regional cooling. Smeerenburgbreen became more active ...